Coexisting Angiomyolipoma and Renal Cell Carcinoma in a Kidney of an Elderly Woman: Case Report and Review of the Literature - Barry Billings; Leon C. Hamrick; Anton J. Bueschen; Philip J. Kenney (The Scientific World Journal)
Angiomyolipoma is a well described but relatively uncommon benign renal neoplasm composed of varying admixtures of mature adipose tissue, smooth muscle, and thick-walled blood vessels.[1] The incidence of angiomyolipoma is about 0.3% overall.[2] It frequently occurs in patients with tuberous sclerosis. Even more uncommon is the simultaneous occurrence of angiomyolipoma and renal cell cancer in the same kidney in a patient without tuberous sclerosis.